2015
DOI: 10.1186/s12886-015-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness and costs of Bevacizumab to Ranibizumab in patients with Diabetic Macular Edema: a randomized clinical trial (the BRDME study)

Abstract: BackgroundThe effectiveness of ranibizumab in the treatment of diabetic macular edema has been proven with large clinical trials. For bevacizumab only two clinical trials have been published and a head-to-head comparison is lacking to date. However, if proved non-inferior to ranibizumab, use of the off-label bevacizumab could reduce costs enormously without a loss in visual acuity. A cost-effectiveness study has been designed to substantiate this hypothesis.AimTo compare the effectiveness and costs of 1.25 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…8 The Guernsey eye service also used only bevacizumab in 2015, which Lotery provided. 9 The GMC has confirmed that doctors practising there are registered with them.…”
Section: Featurementioning
confidence: 99%
“…8 The Guernsey eye service also used only bevacizumab in 2015, which Lotery provided. 9 The GMC has confirmed that doctors practising there are registered with them.…”
Section: Featurementioning
confidence: 99%
“…15 The most relevant inclusion criteria for DME patients were (1) clinically significant macular edema as defined by the Early Treatment Diabetic Retinopathy Study (ETDRS); (2) central macula thickness of >325 lm as documented using optical coherence tomography (OCT); (3) no previous intravitreal anti-VEGF or triamcinolone injections within 3 months prior to randomization; (4) no previous macular focal laser therapy within 3 months of commencement of the study period; and (5) age >18 years old. The most relevant exclusion criteria were (1) presence of ocular disease other than DR and cataract; (2) uncontrolled glaucoma; (3) intraocular surgery, injection, or laser photocoagulation within 3 months of commencement of the study period; and (4) active untreated proliferative DR.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Blood samples of DME patients included in the ongoing BRDME study 15 were analyzed. The BRDME study was a large clinical trial in which patients with DME receive monthly antivascular endothelial growth factor (anti-VEGF) injections during 6 months in 7 university medical centers in the Netherlands (Dutch Trail Register NTR3247and ClinicalTrials.-gov NCT01635790).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In Holland, bevacizumab is approved as first-line treatment for AMD, and a randomised trial to compare bevacizumab with ranibizumab for diabetic macular oedema is underway. 21 In Italy, Roche/Novartis were fined 180 million euros for trying to 'channel demand toward the much more expensive drug Lucentis, through an artificial distinction between the two products'. 22 To conclude, UK regulation has resulted in an unnecessarily expensive choice of anti-VEGF treatment, despite good evidence of safety, efficacy, cost savings, and support from the respected professional bodies for the use of bevacizumab, despite repeated requests to the Government.…”
mentioning
confidence: 99%